A bibliometric study of the top 100 most‐cited randomized controlled trials, systematic reviews and meta‐analyses published in endodontic journals. (13th May 2019) - Ahmad, P.; Dummer, P. M. H.; Chaudhry, A.; Rashid, U.; Saif, S.; Asif, J. A.
Abstract: Aim: To identify and analyse the main features of the top 100 most‐cited randomized controlled trials, systematic reviews and meta‐analyses published in endodontic journals from 1961 to 2018. Methodology: The Clarivate Analytics' Web of Science 'All Databases' was used to search and analyse the 100 most frequently cited randomized controlled trials, systematic reviews and meta‐analyses having 'randomized', 'randomised', 'randomized controlled', 'randomised controlled', 'randomized controlled trial', 'randomized controlled trials', 'clinical trial', 'systematic', 'systematic review', 'meta‐analysis', and 'meta‐analyses' in the title section. The 'International Endodontic Journal', 'Journal of Endodontics', 'Oral Surgery Oral Medicine Oral Pathology Oral Radiology and Endodontology', 'Australian Endodontic Journal', 'Endodontics & Dental Traumatology', 'Endo‐Endodontic Practice Today' and 'European Endodontic Journal' were included in the publication name section. After ranking the articles in a descending order based on their citation counts, each article was cross‐matched with the citation counts in Elsevier's Scopus and Google Scholar. The articles were analysed, and information on citation counts, citation density, year of publication, contributing authors, institutions and countries, journal of publication, study design, topic of the article and keywords was extracted. Results: The citation counts of the 100 most‐cited articles varied from 235 to 20 (Web of Science), 276 to 17 (Scopus) and 696 to 1 (Google Scholar). The year in which the top 100 articles were published was 2010 ( n = 13). Among 373 authors, the greatest number of articles was associated with three individuals namely Reader A ( n = 5), Beck M ( n = 5) and Kvist T ( n = 5). Most of the articles originated from the United States ( n = 24) with the greatest contribution from Ohio State University (USA) ( n = 5). Randomized controlled trials were the most frequent study design ( n = 45) followed by systematic reviews ( n = 30) with outcome studies of root canal treatment being the major topic ( n = 35). The Journal of Endodontics published the largest number of included articles ( n = 70) followed by the International Endodontic Journal ( n = 27). Among 259 unique keywords, meta‐analysis ( n = 23) and systematic review ( n = 23) were the most frequently used. Conclusion: This study has revealed that year of publication had no obvious impact on citation count. The bibliometric analysis highlighted the quantity and quality of research, and the evolution of scientific advancements made in the field of Endodontology over time. Articles before 1996, that is prior to the CONSORT statement that encouraged authors to include specific terms in the title and keywords, may not have been included in this electronic search.